2011
DOI: 10.4314/ajtcam.v8i3.65292
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase activity of endemic plant extracts from Soqotra

Abstract: Abstract:A total of 30 chloroform and methanol extracts from the following endemic Soqotran

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…B. socotrana essential oil showed the higher AChE inhibitory activity at 59.3% at a concentration of 200 lg/mL in comparison to the essential oils of B. elongata and B. ameero (29.6% and 41.6% enzyme inhibition, respectively). It has been shown that at 200 mg/L, chloroform extracts of B. socotranus and B. elongata (Bakthira et al 2011) inhibited AChE by 71.2% and 46.3%, respectively, but methanol extracts showed an inhibitory activity below 50%. Our essential oil was more active than those mentioned above (IC 50 ¼ 67.10 ± 0.03 mg/L).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…B. socotrana essential oil showed the higher AChE inhibitory activity at 59.3% at a concentration of 200 lg/mL in comparison to the essential oils of B. elongata and B. ameero (29.6% and 41.6% enzyme inhibition, respectively). It has been shown that at 200 mg/L, chloroform extracts of B. socotranus and B. elongata (Bakthira et al 2011) inhibited AChE by 71.2% and 46.3%, respectively, but methanol extracts showed an inhibitory activity below 50%. Our essential oil was more active than those mentioned above (IC 50 ¼ 67.10 ± 0.03 mg/L).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…An inhibitory activity has been reported for green leaves of C. sinensis previously [29]. The occurrence of flavonoid saponins, polyphenols, and catechins is well documented in different preparations of C. sinensis .…”
Section: Resultsmentioning
confidence: 85%
“…The finding of this study shows that the four most active herbal extracts contained not only nitorgenic compound such as alkaloid but also these extracts also contain rich components of saponin, flavonoid, and essential oils [29-34]. The new area of interest in research involves both AChE inhibitors and BuChE inhibitors after recognition of BuChE activity in hippocampus of patients with AD [33,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Plant based compounds have been used as cognition enhancers herbs like Withania somnifera, Centella asiatica, Curcuma longa, Bacopa monnieri, Convolvulus pluricaulis, Celastrus paniculatus, Nardostachys jatamansi have been reported to be used in management of cognitive impairment in Ayurvedic system of medicine. 25,26 Acetyl cholinesterase inhibitory activity is dose dependently increasing at a concentration ranging from 50 µg/ml to 300 µg/ml and when compared to standard Galanthamine the inhibitory activity is moderate even though the tested extract shows significant activity. The results are depicted in Table 1 and Figure 1 and can be used for treating neurodegenerative disorders.…”
Section: Resultsmentioning
confidence: 99%